SOCIAL TRANSFORMATION THROUGH SOCIAL ENTREPRENEURSHIP: THE ROLE OF SOCIAL WORKERS IN COMMUNITY EMPOWERMENT A SYSTEMATIC REVIEW OF THE LITERATURE - Sakroni (Adisam Publisher, 2026)
This research focuses on the study of the role of social workers in the assessment of the development of social entrepreneurship in the context of empowering the community as a tactic to achieve social change. This paper applies Systematic Literature Review (SLR) by following the PRISMA protocol, through identifying, selecting and analyzing academic literature to look for the eventual role of social entrepreneurship which contributes to social changes and community welfare. Here, we show that the review findings indicate the importance of social entrepreneurship in the economic potential, skill sets, and social ties of marginalized populations. Social workers also serve as facilitators to connect communities to resources and economic opportunities, as educators to offer entrepreneurial skills training, and as advocates for inclusive policies. Social entrepreneurship is promising in many aspects, but there are still challenges to be faced, such as limited resources and dependencies of the communities on external assistance. The preliminary findings of this study will inform best practices in social entrepreneurship, including into how social workers can best develop their competencies and strengthen cross-sector partnerships, as well as how cross-sector partnerships can develop robust impact indicators.